Genetic Diversity of Elephant Foot Yam (Amorphophallus paeoniifolius) and Two Other Relatives from the Meratus Mountains of South Kalimantan, Indonesia - Dindin Hidayatul Mursyidin; Muhammad Aldy Hernanda; Badruzsaufari Badruzsaufari (Journal of Tropical Biodiversity and Biotechnology, 2022)
Elephant foot yam (Amorphophallus paeoniifolius) is a tuber crop with high economic value, so it is very prospective to be developed. This study aimed to characterize and determine the genetic diversity and relationship of A. paeoniifolius and two other relatives from the Meratus Mountains of South Kalimantan, Indonesia, using the rbcL marker. Eight samples of A. paeoniifolius and three other ones (outgroups), two of A. muelleri and one of A. borneensis, were used in the study. The genetic diversity was determined using the nucleotide diversity index (π), whereas the phylogenetic relationships were reconstructed using the Maximum Likelihood (ML) and Neighbor-Joining (NJ) methods. The results show that this germplasm has a high diversity at an inter-species level of 0.95% and a low at intra-species (0.33%). The phylogenetic analyses revealed that Amorphophallus from this region separated into different clades, three for NJ and one for ML. In this case, A. paeoniifolius var. sylvestris from Bati-Bati, Tanah Laut is closely related to A. paeoniifolius var. hortensis from Marajai, Balangan. In conclusion, although Amorphophallus from the Meratus Mountains of South Kalimantan, Indonesia, shows a high diversity at an inter-species level, the phylogenetic analyses revealed a unique relationship. This finding is expected to be a reference in supporting efforts to conserve, cultivate, and utilize sustainable Amorphophallus, globally and locally, particularly for the Dayak Meratus community of the South Kalimantan, Indonesia.